Dasometric analysis of siricote (Cordia dodecandra A. DC.) plantations under three types of management at Xmatkuil Yucatan - Campos B., Simei M.; Jiménez-Osornio, Juan José; Barrientos M., Roberto (Instituto de Ecología, A.C., 2016)
A dasometric analysis of three Cordia dodecandra A. DC. plantations under different types of management at Xmatkuil, Yucatan was undertaken. The plantations were nine years old. Height, bole and DBH were measured. Coverage and quality of the trunks of all individuals of each plantation were assessed. Log quality of the trunk was evaluated comparing digital images obtained from the trunk of each tree with the quality rating scale for trunks assigning a number from 1-6 depending upon the straightness of the trunk of each tree. With the data obtained, a multivariate analysis of covariance (MANCOVA) was performed to see if there were significant differences in the variables height, bole and diameter at breast height (DBH) considering coverage as an auxiliary explanatory variable. The nonparametric Kruskall-Wallis analysis was utilized for the statistical analysis of trunk quality. The MANCOVA indicated significant differences in height, bole and DBH in the three plantations. Likewise, the Kruskal-Wallis test with p-value ≤ 0, 05 indicated significant differences. Results demonstrated how management influences the growth of C. dodecandra. These results provide information necessary for the future establishment of agroforestry plantations as well as for taking adequate decisions for the sustainable management of the species.